Notes on american poetry - Lantz, Edith Lynnette (My University, 1896)
Introduction: “Poetry is the rhythmical expression of beauty or imagination, the verbal utterance of the ideal, and therefore the highest and most permanent form of literature.” According to this definition, even the most liberal minded must admit that there was no poetry produced in America before eighteen hundred. Since then however, it must be granted – even by the most conservative – that America has enjoyed a period of poetical production of which she may in no wise feel ashamed.
Citation: Lantz, Edith Lynnette. Notes on american poetry. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Poetry; Imagination; Poetical production; America; Theses; Manuscripts (documents)